A reforma do conselho de segurança das Nações Unidas: uma questão institucional - Mariana Pimenta Oliveira Baccarini (2014)
The reform of the Security Council of the United Nations is today one of the main issues discussed by the United Nations as a result of questions about the legitimacy and representativeness of the body. However, theorists and scholars have debated the issue more from the logic of the actors, their interests and negotiations than from the institutional logic, which limits the understanding of the problem. This study seeks to fill this gap by reconstructing the history of the organization and reform, since the League of Nations, in order to demonstrate how the institutional reform is an essential and permanent part of an institution, and not something conjunctural. Thus, the reform of the Security Council constitutes an institutional process that suffered a historical lock in at the time of the Charter of the United Nations creation, based on the establishment of the veto power of the permanent members of the Security Council and other rules to change the composition of the body. This historical lock in determined, in its turn, a path dependence of the subsequent attempts to reform the decision-making process of the Security Council, preventing substantive changes, as demonstrated in the reform of 1963/1965 and in the unsuccessful negotiations that started with the end of the Cold War. We conclude by arguing that, given the difficulty of formally reform the Security Council, we must focus on the informal institutions that emerged and are emerging to complement, substitute, accommodate or compete with the formal institutions, given that they can lessen the effects of the historical lock in and make possible a informal reform in the body that would ensure greater stability.